PENGARUH EARNINGS PER SHARE (EPS) DAN TOTAL ASET TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB-SEKTOR INDUSTRI FOOD & BEVERAGE - Zahra, Zahra; Simanjuntak, Pranatalindo (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to find out if Earnings Per Share (EPS) & Total Assets can affect Stock Prices. This research is an associative research that uses a quantitative approach with the collection of secondary data contained in the company's financial statements on the Indonesia Stock Exchange (IDX) and the Company's official website. The population of this study is 95 companies in the Food & Beverage Industry sub-sector that are still listed on the Indonesia Stock Exchange (IDX), and the sample of this study is 27 companies with an observation year of 3 years of financial statements so that the total overall sample is 81, sampling technique using Purposive Sampling. The analysis technique uses multiple linear regression analysis with SPSS 24.0 Software. This study found that Earnings Per Share (EPS) & Total partially had a positive and significant effect on the Stock Price. Earnings Per Share (EPS) and Total Assets have a simultaneous influence on the Stock Price